A cold water extract of Fucus vesiculosus inhibits lipopolysaccharide (LPS) induced pro-inflammatory responses in the porcine colon ex-vivo model. (October 2016) - Bahar, Bojlul; O'Doherty, John V.; Smyth, Thomas J.; Ahmed, Albin M.; Sweeney, Torres
Abstract: The objectives of this experiment were to compare the in-vitro anti-inflammatory activity of crude extracts (cold water (CWE), hot water and 80% ethanol extract) of F. vesiculosus and to predict the key molecular targets of the extract with most anti-inflammatory activity in-vitro . In TNF-α challenged Caco-2 cells, of the three crude extracts, the CWE exhibited maximum inhibition of IL-8 production. In the ex-vivo challenged porcine colonic tissue, CWE inhibited the expression (> 2 fold) of inflammatory mediators ( PTGS2, C5, LYZ ), cytokines ( IL17A, IL8 ), chemokines ( CCL2, CXCL2, CXCL10, CXCL11 ), cell adhesion molecules ( ICAM1, VCAM1 ), toll like receptors ( TLR4, TLR7 ) and components of NF-κB ( NFKB1, RELB ), MAPK ( MAP3K8 ) and AP-1 ( CJUN ) pathways. The gene expression analysis suggest that the CWE does contain immunomodulatory bioactive compound/s that mediated through the interferon regulatory system 2, TNF-α inducing protein 3 and TNF-α receptor 2 and thus has potential application for human and animal health. Highlights: Anti-inflammatory activity of three extracts of F. vesiculosus were evaluated. Cold water extract (CWE) of F. vesiculosus exhibited strong anti-inflammatory activity in-vitro. CWE down-regulated the expression of inflammatory markers in porcine colonic tissue ex-vivo . Effects of the CWE were mediated through inhibition of NF-κB, MAPK and AP-1 pro-inflammatory pathways.